T-wave and heart rate variability changes to assess training in world-class athletes - Iellamo, F.; Pigozzi, F.; Spataro, A.; Lucini, D.; Pagani, M. (Medicine & Science in Sports & Exercise, 2004)
PURPOSE: A decrease of electrocardiographic T-wave voltage with increasing training loads has been reported in elite endurance athletes and ascribed to training-related adaptation in sympathetic activity to the ventricles. A switch from vagal to sympathetic predominance in sino-atrial node regulation on going from low to peak training load has been reported in world-class rowers. In this study on world-class endurance athletes, we tested the hypothesis that training-induced variations in T-wave amplitude at higher training loads are paralleled by changes in HR spectral profile. METHODS: We studied eight male rowers of the Italian national team in the season culminating with the Rowing World Championship. Athletes were evaluated at 50 and 100% of training load, approximately 20 d before the World Championship, and during the World Championship, when the intensity was markedly reduced. We assessed T-wave maximum amplitude in chest lead V6 and cardiac autonomic regulation by power spectral analysis of R-R interval variability. RESULTS: The increase in training load from 50 to 100% was accompanied by a significant decrease in high frequency and a significant increase in low-frequency R-R variability (in normalized units) with a concomitant significant decrease in T-wave amplitude (microV). Reduction in training load during the World Championship resulted in a return of spectral profile to the level observed at 50% training load and in a partial recovery of T-wave amplitude. HR did not change significantly. CONCLUSIONS: In high-performance world-class athletes, training load simultaneously affects both ventricular repolarization and HR variability patterns possibly through variations in cardiac sympathetic modulation to the ventricles and the sino-atrial node. Information on concomitant changes in ventricular repolarization and autonomic cardiac regulation might be employed to tailor training protocols of elite athletes.